Inducing ipsilateral motor‐evoked potentials in the biceps brachii muscle in healthy humans - Hu, Nijia; Tanel, Meghan; Baker, Stuart N.; Kidgell, Dawson J.; Walker, Simon (The European journal of neuroscience, 2024)
To assess reticulospinal tract excitability, high‐intensity transcranial magnetic stimulation (TMS) has been used to elicit ipsilateral motor‐evoked potentials (iMEPs). However, there is no consensus on robust and valid methods for use in human studies. The present study proposes a standardized method for eliciting and analysing iMEPs in the biceps brachii. Twenty‐four healthy young adults participated in this study. Electromyography (EMG) electrodes recorded contralateral MEPs (cMEPs) from the right and iMEPs from the left biceps brachii. A dynamic preacher curl task was used with ~15% of the subject's one‐repetition maximum load. The protocol included maximal compound action potential (M‐max) determination of the right biceps brachii muscle, TMS hotspot determination, and four sets of five repetitions where 100% stimulator output was delivered at an elbow angle of 110° of flexion. We normalized cMEP amplitude by M‐max (% M‐max) and iMEP by cMEP amplitude ratio (ICAR). Clear iMEPs above background EMG were observed in 21 subjects (88%, ICAR = .31 ± .19). Good‐to‐excellent agreement (intraclass correlation coefficient [ICC] = .795–1.000) and low bias (.01–.08 mV and .60–1.11 ms) were demonstrated when comparing two different analysis methods (i.e. fixed time‐window vs. manual onset detection) to determine the cMEP and iMEP amplitude and latency, respectively. Most subjects demonstrated clear iMEPs above background EMG triggered at a pre‐determined joint angle during a light‐load dynamic preacher curl exercise. Similar results were obtained when comparing a single‐trial manual identification of iMEP and a semi‐automated time‐window data analysis approach. To assess cortico‐reticular excitability, this study presents a standardized method to robustly elicit and analyse iMEPs in the biceps brachii of healthy young adults. Study design: During slow, dynamic preacher curl contractions, 100% of stimulator output was triggered when the elbow angle reached 110°flexion. Findings: Dynamic bicep brachii contractions with ~15% 1RM and 100% stimulator output induces consistent iMEPs. Manual and automated analysis methods provide similar results.